Crucible : all-new tales of Valdemar - Lackey, Mercedes; Brozek, Jennifer, 1970-; Shaver, Stephanie D.; Birtolo, Dylan; Vaughan, Elizabeth (Elizabeth A.); Collins, Ron; Waters, Elisabeth; Lang, Michele; Schwengel, Kristin; Patton, Fiona, 1962-; Swann, Louisa (DAW book collectors, 2015)
"Eighteen all-original stories of the heralds, bards, and healers--Valdemar's elite protective force--including a new story by Mercedes Lackey"--Cover.